2003
DOI: 10.1002/cncr.11406
|View full text |Cite
|
Sign up to set email alerts
|

cDNA microarray analysis of gene expression in pathologic stage IA nonsmall cell lung carcinomas

Abstract: BACKGROUNDThe relationship between altered gene expression and tumor progression in lung carcinoma has yet to be characterized. Gene expression in pathologic Stage IA nonsmall cell lung carcinoma specimens was analyzed using a cDNA microarray.METHODSSurgical specimens were used for the current study. The pathologic stage was IA (AJCC) in five tumors, IB in two, IIA in one, IIIA in one, and IIIB in one. Seven tumor specimens were adenocarcinomas and three were squamous cell carcinomas. Paired mRNAs from carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Several lung cancer microarray studies have reported geneexpression changes with potentially significant prognostic impact, encoding for proteins that are expressed by stromal cells (3,25). These studies were performed on RNA isolated from wholetumor tissues, without prior separation of stromal and tumor cells; thus, the cellular origin of these gene-expression changes was largely uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lung cancer microarray studies have reported geneexpression changes with potentially significant prognostic impact, encoding for proteins that are expressed by stromal cells (3,25). These studies were performed on RNA isolated from wholetumor tissues, without prior separation of stromal and tumor cells; thus, the cellular origin of these gene-expression changes was largely uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Non-small cell lung carcinoma (NSCLC) accounts for 85% of all lung cancers. One of the most consistent histological features of cancer cell invasion is the appearance of desmoplasia: stromal changes characterized by the activation of stromal fibroblasts into carcinoma-associated fibroblasts (CAFs), increased matrix protein disposition, new blood vessel formation, and immune cell infiltration (2,3). These changes have been reported to promote tumor cell growth, invasion, metastases, and resistance to treatment as well as to mediate immune reaction against tumor cells (2,4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gene was considered to be overexpressed when the T:N ratio was greater than 2.0 and underexpressed when the ratio was less than 0.5. The criteria for detecting genes were the same as those used in a study by Nakamura et al 18) .…”
Section: Cdna Microarraymentioning
confidence: 99%
“…Gene expressions were quantified as the tumor-to-normal fluorescence ratio (T:N ratio). The genes were judged as being overexpressed when the ration was >2.0 and as underexpressed when the ratio was <0.5 (22).…”
Section: Methodsmentioning
confidence: 99%